Impacts on Student Learning and Skills and Implementation Challenges of Two Student-Centered Learning Methods Applied in Online Education - Soubra, Lama; Al-Ghouti, Mohammad A.; Abu-Dieyeh, Mohammed; Crovella, Sergio; Abou-Saleh, Haissam (Sustainability, 2022)
Online education became more prevalent during the COVID-19 pandemic in many countries around the world, including the Gulf Cooperation Council (GCC) countries. This study aims at assessing the impacts on learning and skills of two student-centered instructional strategies (problem-based learning (PBL) and just-in-time teaching (JiTT)) used online and their implementation challenges. The PBL and JiTT were implemented in modules taught in various courses delivered at different bachelor’s study levels and disciplines. The research used a mixed design research method. Quantitative data were collected from exam scores and two self-administered surveys. Qualitative data were collected using individual structured interviews. The lecture-based learning method was used for comparisons. A total of 134 students participated in the quizzes and exams, 85 students completed the self-perceived impacts on learning and skills survey, and 82 students completed the implementation challenges survey. Ten students participated in the structured interviews. Tests and survey scores showed that both online PBL and JiTT had significant impacts on students learning and skills and that these effects are consistent across various disciplines. A non-conducive online learning climate, internet connectivity problems, heavy workloads, and time management issues were reported as the implementation challenges. The PBL and JiTT can be considered as effective teaching/learning strategies in online education.